2017
DOI: 10.3390/ijerph14121506
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Industrial Protective Gloves and Hand Skin Temperatures on Hand Grip Strength and Discomfort Rating

Abstract: Daily working activities and functions require a high contribution of hand and forearm muscles in executing grip force. To study the effects of wearing different gloves on grip strength, under a variety of hand skin temperatures, an assessment of the maximum grip strength was performed with 32 healthy male workers with a mean age (standard deviation) of 30.44 (5.35) years wearing five industrial gloves at three hand skin temperatures. Their ages and anthropometric characteristics including body mass index (BMI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 67 publications
1
22
0
Order By: Relevance
“…The statistical analysis showed that there is a significant effect for the age group on the grip strength (F = 7.36, p < 0.001). The post hoc analysis shows that the (60-70) age group is the only group significantly weaker than (18-29), (30)(31)(32)(33)(34)(35)(36)(37)(38)(39), (40)(41)(42)(43)(44)(45)(46)(47)(48)(49), and (50-59) age groups.…”
Section: For Malementioning
confidence: 90%
“…The statistical analysis showed that there is a significant effect for the age group on the grip strength (F = 7.36, p < 0.001). The post hoc analysis shows that the (60-70) age group is the only group significantly weaker than (18-29), (30)(31)(32)(33)(34)(35)(36)(37)(38)(39), (40)(41)(42)(43)(44)(45)(46)(47)(48)(49), and (50-59) age groups.…”
Section: For Malementioning
confidence: 90%
“…Work gloves are used for the protection of hands from potential physical, chemical, and biological hazards [6][7][8][9][10][11][12]. Typical physical hazards of hand exposure at work include cuts and stabs [13], vibrations of tools and machines [14][15][16][17], load and pressure [18][19][20], high and low temperature [11,[21][22][23], and so on. Typical chemical and biological hazards, on the other hand, include hazardous substances (such as pesticides and acids) and organisms such as insects, germs, and even viruses [9,12].…”
Section: Introductionmentioning
confidence: 99%
“…The literature has also found that increasing glove thickness could decrease grip strength in addition to decreasing hand dexterity [27,35,36]. The range of grip strength reduction varies, depending on factors such as the number of layers and fitness of the gloves [15,24,30,33,37,38]. Even though the effects of gloves on grip strength have been reported, further investigations are required to examine how those effects are affected by handedness and the grip span of the handle.…”
Section: Introductionmentioning
confidence: 99%
“…Industrial assemblers, machinists, medical doctors, farmers, and construction workers use gloves in different workplaces to protect their arms and hands from chemicals, heat, cold, and physical harm such as cuts, blisters, and other fatal injuries [6] [7] [8]. However, the use of gloves affects various aspects of hand performance.…”
Section: Effect Of Gloves On Hand Performancementioning
confidence: 99%
“…The effect of glove use on hand performance has been investigated in previous studies. Schoenmarklin and Sudhakar [8] concluded that a certain amount of muscle force was lost while performing activities wearing gloves based on the measurement of normalized peak and mean muscular activities taken from isometric contractions.…”
Section: Effect Of Gloves On Hand Performancementioning
confidence: 99%